Lithium ion battery diaphragm, preparation method thereof and lithium ion battery

By applying a double coating of polysilazane and Si3N4 on the lithium-ion battery separator, the problems of heat shrinkage and HF in the electrolyte at high temperatures are solved, and higher thermal stability and safety are achieved.

CN119542672APending Publication Date: 2025-02-28SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411785754.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators are prone to heat shrinkage under high temperature conditions, and the hydrofluoric acid in the electrolyte has an adverse impact on the battery performance, resulting in safety and cycle stability issues.

Method used

Si3N4 is prepared by partial cleavage of polysilazane to form a separator with high thermal stability and hydrofluoric acid resistance.

Benefits of technology

The separator exhibits good thermal stability at high temperatures, avoids heat shrinkage, and improves the safety and cycle stability of the battery by reacting with HF in the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542672A_ABST
    Figure CN119542672A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery diaphragm, a preparation method thereof and a lithium ion battery, the lithium ion battery diaphragm comprises a base membrane and a coating, and the coating comprises polysilazane and Si3N4. And partially cracked polysilazane is used as a diaphragm coating to carry out coating modification on the diaphragm. On one hand, in the cracking process, polysilazane is cured, has excellent thermal stability and can tolerate the high temperature of 1800 DEG C, so that the coating can well solve the problem of thermal shrinkage of the diaphragm at a relatively high temperature; and on the other hand, the silicon-nitrogen compound can be obtained after the polysiloxane is cracked, and the silicon-nitrogen compound can react with HF in the electrolyte, so that side reaction between the HF and the electrode is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of lithium ion battery materials, and in particular to a lithium ion battery separator and a preparation method thereof, and a lithium ion battery. Background Art

[0002] As one of the "four major parts" of lithium-ion batteries, the diaphragm is an important component of lithium-ion batteries. Traditional lithium-ion battery diaphragms mainly play the role of preventing short circuits between positive and negative electrodes. However, with the development of high-energy-density lithium-ion batteries, the safety issues brought about have become increasingly obvious. News about electric vehicle fires has also been frequently reported in recent years. This is mainly because lithium-ion batteries have thermal runaway, among which the thermal shrinkage of the diaphragm under high temperature conditions is one of the key factors leading to thermal runaway of the battery. Traditional lithium-ion battery diaphragms can no longer meet current usage requirements. In addition, hydrofluoric acid (HF) in the electrolyte has a significant impact on battery performance, especially in high-voltage systems. HF will not only corrode the metal parts and battery casing inside the battery, causing battery leakage, but also destroy the SEI film (solid electrolyte interface) inside the battery, affecting the battery's charge and discharge performance and cycle stability. Therefore, it is critical to control the content of hydrofluoric acid in the electrolyte.

[0003] Therefore, there is an urgent need to develop lithium battery separators with high thermal stability to further improve the safety of lithium-ion batteries. Summary of the invention

[0004] In order to solve the problem that the diaphragm of the above-mentioned background technology lithium battery has thermal shrinkage under high temperature conditions and hydrofluoric acid (HF) in the electrolyte has an adverse effect on battery performance, the present invention provides the following technical solutions:

[0005] The first aspect of the present invention provides a lithium-ion battery separator, comprising a base film and a coating; the base film comprises a first surface and a second surface opposite to the first surface, the coating is coated on the first surface and the second surface to form a double-layer coating, and the coating comprises polysilazane and Si3N4.

[0006] Taking the total mass of the coating material as 100%, the mass proportion of Si3N4 in the coating is 8% to 12%.

[0007] The Si3N4 in the coating is prepared by partial cracking of the polysilazane.

[0008] Preferably, the coating has a thickness of 1.5 to 3.0 μm.

[0009] Preferably, the coating has a thickness of 2 μm.

[0010] Preferably, the base film is PP or PE, and the thickness of the base film is 7 to 12 μm.

[0011] Preferably, the base film has a thickness of 9 μm.

[0012] It should be noted that the diaphragm coating provided by the present invention itself is not conductive.

[0013] On the one hand, part of the polysilazane in the lithium-ion battery separator provided by the present invention solidifies during the cracking process, has excellent thermal stability, and can withstand a high temperature of 1800°C. Therefore, the coating can well solve the problem of thermal shrinkage of the separator at higher temperatures. On the other hand, silicon nitrogen compounds (mainly Si3N4) can be obtained after the cracking of polysiloxane, and Si3N4 can react with HF in the electrolyte, thereby avoiding the occurrence of side reactions between HF and the electrode, thereby further improving the safety of lithium-ion batteries.

[0014] In the present invention, the mass percentage of Si3N4 is 8% to 12%, for example, it can be 8%, 9%, 9.5%, 10%, 11.5%, 12%, etc.

[0015] In the present invention, the thickness of the coating is 1.5 to 3.0 μm, for example, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 2 μm, 2.2 μm, 3 μm, etc.

[0016] In the present invention, the base film has a thickness of 7 to 12 μm, for example, 7 μm, 8 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 12 μm, etc.

[0017] The second aspect of the present invention provides a method for manufacturing the lithium ion battery separator of the first aspect of the present invention, comprising the following steps:

[0018] S1 takes a certain amount of polysilazane, partially cracks it under a nitrogen atmosphere, and then crushes and grinds it to obtain a composition of polysilazane containing Si3N4;

[0019] S2: dispersing the composition in an aqueous solvent containing a dispersant, and then adding a thickener, a binder and a wetting agent to the water respectively, and rotating and stirring to obtain a stable diaphragm coating slurry;

[0020] S3: coating the separator coating slurry on both sides of the base film and drying the moisture to obtain the lithium ion battery separator.

[0021] Preferably, the partial cracking of polysilazane in step S1 is carried out under a nitrogen atmosphere, and the temperature is increased to the cut-off temperature at a preset heating rate and then kept warm, and then cooled at a preset cooling rate, and then cooled naturally after cooling to the removal temperature, and the partial cracking is completed.

[0022] Preferably, the limiting conditions for partially cracking polysilazane include: the preset heating rate is 40-60°C / S, the cut-off temperature is 1000-1300°C, the insulation time is 10-30S, the preset cooling rate is 10-20°C / S, and the removal temperature is 400-600°C.

[0023] Preferably, in step S1, the mass proportion of Si3N4 in the composition in the coating is 8% to 12%, and / or, after grinding, the particle size of the composition is 20 to 80 nm.

[0024] Preferably, the limiting condition for the rotary stirring in step 2 is stirring at a speed of 800 rpm for 2 hours.

[0025] Preferably, in step S2, the mass ratio of the composition: dispersant: thickener: binder: wetting agent is 80-120:1:10:10:1; and / or the solid content of the diaphragm coating slurry is 40%-60%.

[0026] The solid content is the ratio of the composition to the liquid mixture, that is, the mass of the solid matter in the slurry divided by the total mass of the slurry. When dispersants, thickeners, binders, and wetting agents are used as aqueous solutions, the mass of the solids in the dispersants, thickeners, binders, and wetting agents must first be calculated based on the added amount and the solid content themselves, and then the mass of the composition is added to obtain the mass of the solid matter in the slurry. At the same time, the mass of the currently available water can be obtained. Finally, the mass of the additional water solvent that needs to be added can be calculated based on the target solid content.

[0027] Preferably, in step S2, the mass ratio of composition: dispersant: thickener: binder: wetting agent is 100:1:10:10:1.

[0028] Preferably, the solid content of the diaphragm coating slurry is 50%.

[0029] In the step S2, the dispersant is one or more of acrylate, modified acrylate and acrylic polymer;

[0030] The thickener is a sodium hydroxymethylcellulose thickener, such as CMC-Na, CMC-Li, etc.;

[0031] The binder is one or more of polyacrylate, modified polyacrylate and modified polyvinyl alcohol;

[0032] The wetting agent is at least one of fatty alcohol polyoxyethylene ether and polyether modified silicone.

[0033] Preferably, the base film in step S3 is selected from PP or PE.

[0034] Preferably, in step S3, drying of moisture is performed in an oven.

[0035] Preferably, in the step S3, the thickness of the coatings on both sides of the base film is consistent during double-sided coating, and the error range is ±0.2 μm per side.

[0036] The third aspect of the present invention provides a lithium battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive and negative electrode sheets, wherein the separator is a lithium ion battery separator manufactured by the manufacturing method provided by the second aspect of the present invention.

[0037] The beneficial effect of the present invention is that the diaphragm is coated and modified by using partially cracked polysilazane as a diaphragm coating. On the one hand, during the cracking process, the polysilazane solidifies and has excellent thermal stability and can withstand a high temperature of 1800°C. Therefore, the coating can well solve the problem of thermal shrinkage of the diaphragm at higher temperatures. On the other hand, silicon nitrogen compounds can be obtained after the cracking of polysiloxane, and the silicon nitrogen compounds can react with HF in the electrolyte, thereby avoiding the occurrence of side reactions between HF and the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0039] Figure 1 This is a SEM image of the surface of a PE diaphragm coated with a Si3N4-OPSZ coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The first aspect of the present invention provides a lithium-ion battery separator, comprising a base film and a coating; the base film comprises a first surface and a second surface opposite to the first surface, the coating is coated on the first surface and the second surface to form a double-layer coating, and the coating comprises polysilazane and Si3N4.

[0042] In some embodiments, based on the total mass of the coating material being 100%, the mass proportion of Si3N4 in the coating is 8% to 12%.

[0043] In some embodiments, the Si3N4 in the coating is prepared by partial cleavage of the polysilazane.

[0044] In some embodiments, the coating has a thickness of 1.5 to 3.0 μm.

[0045] In some embodiments, the coating thickness is 2 microns.

[0046] In some embodiments, the base film is PP or PE, and the base film thickness is 7 to 12 μm.

[0047] In some embodiments, the base film has a thickness of 9 μm.

[0048] The second aspect of the present invention provides a method for manufacturing the lithium ion battery separator of the first aspect of the present invention, comprising the following steps:

[0049] S1: taking a certain mass of polysilazane (≥99.7%), partially cracking it under a nitrogen atmosphere, and then crushing and grinding it to obtain a composition of polysilazane containing Si3N4;

[0050] S2: dispersing the composition in an aqueous solvent containing a dispersant, and then adding a thickener, a binder and a wetting agent to the water respectively, and rotating and stirring to obtain a stable diaphragm coating slurry;

[0051] S3: coating the separator coating slurry on both sides of the base film and drying the moisture to obtain the lithium ion battery separator.

[0052] In some embodiments, the partial cracking of polysilazane in step S1 is performed under a nitrogen atmosphere, and the temperature is increased to a cut-off temperature at a preset heating rate and then kept warm, and then cooled at a preset cooling rate. After cooling to a removal temperature, the mixture is naturally cooled, and the partial cracking is completed.

[0053] In some embodiments, the limiting conditions for partially cracking polysilazane include: the preset heating rate is 40-60°C / S, the cut-off temperature is 1000-1300°C, the insulation time is 10-30S, the preset cooling rate is 10-20°C / S, and the removal temperature is 400-600°C.

[0054] In some embodiments, in step S1, the mass percentage of Si3N4 in the composition in the coating is 8% to 12%, and / or, after grinding, the particle size of the composition is 20 to 80 nm.

[0055] In some embodiments, the rotational stirring in step 2 is limited to stirring at a speed of 800 rpm for 2 hours.

[0056] In some embodiments, the mass ratio of the composition: dispersant: thickener: binder: wetting agent in step S2 is 80-120:1:10:10:1; and / or the solid content of the diaphragm coating slurry is 40%-60%, where the solid content is the ratio of the composition to the liquid mixture.

[0057] In some embodiments, the mass ratio of composition: dispersant: thickener: binder: wetting agent in step S2 is 100:1:10:10:1.

[0058] In some embodiments, the solid content of the separator coating slurry is 50%.

[0059] In the step S2, the dispersant is one or more of acrylate, modified acrylate and acrylic polymer;

[0060] The thickener is a sodium hydroxymethylcellulose thickener, such as CMC-Na, CMC-Li, etc.;

[0061] The binder is one or more of polyacrylate, modified polyacrylate and modified polyvinyl alcohol;

[0062] The wetting agent is at least one of fatty alcohol polyoxyethylene ether and polyether modified silicone.

[0063] In some embodiments, the base film in step S3 is selected from PP or PE.

[0064] In some embodiments, the drying of moisture in step S3 is performed using an oven.

[0065] In some embodiments, during double-sided coating in step S3, the thickness of the coating on both sides of the base film is consistent, and the error range is ±0.2 μm per side.

[0066] The third aspect of the present invention provides a lithium battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive and negative electrode sheets, wherein the separator is a lithium ion battery separator manufactured by the manufacturing method provided by the second aspect of the present invention.

[0067] Example 1

[0068] (I) Preparation of lithium battery separator

[0069] (1) Preparation of partially cracked polysilazane:

[0070] A certain mass of polysilazane (purity ≥ 99.7%) was measured and placed in a metal crucible, and the crucible was transferred to a Joule heat fixed bed for cracking. The cracking process was carried out in a nitrogen atmosphere, and the heating rate was set to 50°C / s, the cut-off temperature was 1200°C, and the temperature was kept warm for 20S after reaching the cut-off temperature. Then the heating was stopped, and the crucible was cooled at a cooling rate of 15°C / s. After cooling to 500°C, the crucible was taken out to achieve partial cracking of the polysilazane. Finally, the partially cracked polysilazane was crushed and ground to obtain a composition: polysilazane containing silicon nitrogen compounds (abbreviated as Si3N4-OPSZ), and the particle size of the ground particles was controlled to be 50nm.

[0071] In the composition, the mass ratio of silicon nitrogen compound Si3N4 to polysilazane OPSZ is 8:89, that is, the mass proportion of Si3N4 is about 8.25%.

[0072] (2) Preparation of diaphragm coating slurry:

[0073] The composition obtained in step (1) is dispersed in an aqueous solvent containing a dispersant, and then a thickener, a binder and a wetting agent are respectively added to the water. The mass ratio of the composition: dispersant: thickener: binder: wetting agent in the slurry is 100:1:10:10:1. After stirring at a speed of 800 rpm for 2 hours, a stable Si3N4-OPSZ-containing diaphragm coating slurry can be obtained. The solid content of the slurry is controlled to be 50% by adjusting the amount of water added.

[0074] Among them, solid content (m1 / M) refers to the total mass m1 of solid matter in the slurry divided by the total mass M of the diaphragm coating slurry. Specifically, dispersants, thickeners, binders, and wetting agents are all aqueous solutions. We first need to calculate the mass m2 of solids in the dispersant, thickener, binder, and wetting agent based on the addition amount of the above aqueous solution and its solid content parameters, and then add the mass m3 of the composition to obtain the mass m1 of the total solid matter in the slurry, that is, m1=m2+m3. Finally, according to our target solid content, we can calculate the mass of additional water solvent that needs to be added to control the solid content within the target range.

[0075] In this embodiment, the dispersant is acrylate;

[0076] The thickener is a sodium hydroxymethylcellulose thickener CMC-Na. In some other embodiments, CMC-Li may also be used;

[0077] The binder is polyacrylate;

[0078] The wetting agent is fatty alcohol polyoxyethylene ether;

[0079] (3) Preparation of lithium battery separator:

[0080] The base film uses PE film, and the slurry prepared in the previous step is coated on a 9-micron thick diaphragm by a micro-gravure method. The coating thickness is 2 microns, and the single-side error range is ±0.2 microns. The moisture is dried in an oven to complete double-sided coating. When double-sided coating is performed, the thickness of the coating on both sides of the base film is consistent, and a lithium battery diaphragm modified with a Si3N4-OPSZ coating can be obtained.

[0081] SEM image of the surface of the PE diaphragm coated with Si3N4-OPSZ coating was prepared, and the coating was uniform.

[0082] (II) Preparation of lithium batteries:

[0083] Preparation of positive electrode: lithium manganese oxide, binder PVDF, and conductive agent Super-P are mixed in a ratio of 95:3:2, and solvent NMP is added to form positive electrode slurry, which is then coated on aluminum foil to form a positive electrode;

[0084] Preparation of negative electrode: Graphite, binder CMC, SBR, and conductive agent Super-P were mixed in a ratio of 95:1:1:3, solvent water was added to form negative electrode slurry, and the mixture was coated on aluminum foil to form a negative electrode;

[0085] The electrolyte composition is EC, DEC, EMC in a volume ratio of 1:1:1, 1M lithium hexafluorophosphate, and 0.2% FEC.

[0086] A lithium battery is prepared by using the lithium battery separator prepared in (a) and the above-mentioned positive electrode, negative electrode and electrolyte.

[0087] Example 2

[0088] In step (1) of the preparation of the lithium battery separator, the mass ratio of the silicon nitrogen compound Si3N4 to the polysilazane OPSZ in the composition is adjusted to 5:93. The other steps are the same as those in Example 1 for the preparation of the partially cracked polysilazane, the preparation of the separator coating slurry, the preparation of the lithium battery separator and the preparation of the lithium battery.

[0089] Example 3

[0090] In step (1) of the preparation of the lithium battery separator, the mass ratio of the silicon nitrogen compound Si3N4 to the polysilazane OPSZ in the composition is adjusted to 10:86. The other steps are the same as those in Example 1 for the preparation of the partially cracked polysilazane, the preparation of the separator coating slurry, the preparation of the lithium battery separator and the preparation of the lithium battery.

[0091] Example 4

[0092] In step (3) of preparing the lithium battery separator, the coating thickness was adjusted to 1 μm. The other steps were the same as those in Example 1, including the preparation of partially cracked polysilazane, the preparation of separator coating slurry, the preparation of lithium battery separator and the preparation of lithium battery.

[0093] Example 5

[0094] In step (3) of preparing the lithium battery separator, the coating thickness was adjusted to 3 μm. The other steps were the same as those in Example 1, including the preparation of partially cracked polysilazane, the preparation of separator coating slurry, the preparation of lithium battery separator and the preparation of lithium battery.

[0095] Example 6

[0096] In step (3) of preparing the lithium battery separator, a 7-micron PE film is used as the base film. The other steps are the same as those in Example 1, including the preparation of partially cracked polysilazane, the preparation of separator coating slurry, the preparation of lithium battery separator and the preparation of lithium battery.

[0097] Example 7

[0098] In step (3) of preparing the lithium battery separator, a 12 μm PE film is used as the base film. The other steps are the same as those in Example 1, including the preparation of partially cracked polysilazane, the preparation of separator coating slurry, the preparation of lithium battery separator and the preparation of lithium battery.

[0099] Comparative Example 1

[0100] The 9-micron PE film was directly used to replace the lithium battery separator in (I). The other steps were the same as those in Example 1.

[0101] Comparative Example 2

[0102] In the preparation of the lithium battery separator, step (3) is to complete the coating on one side only. The other steps are the same as those in Example 1, i.e., the preparation of partially cracked polysilazane, the preparation of separator coating slurry, the preparation of lithium battery separator and the preparation of lithium battery.

[0103] The lithium ion batteries provided in Examples 1 to 7 and Comparative Examples 1 to 2 were subjected to the following performance tests. The test methods are as follows:

[0104] ①Electrolyte acidity test after cycle

[0105] The acidity test is to detect the acidity of the electrolyte before use and after 300 cycles, and the acid value of the electrolyte sample is titrated using the triethylamine EMC method.

[0106] ②140℃ hot box test

[0107] After the battery is fully charged at 1C, put it in an oven, start at room temperature, heat up to 120℃ at 5℃ / min, keep warm at 120℃ for 1h. If there is no fire or explosion, continue testing, heat up to 130℃ at 5℃ / min, and keep warm for 1h. If there is no fire or explosion, continue testing, heat up to 140℃ at 5℃ / min, and keep warm for 1h.

[0108] ③First discharge capacity test

[0109] At 45°C, discharge at a constant current of 1C to 3.5V;

[0110] ④300 cycles capacity retention rate

[0111] In a constant temperature environment of 45°C, in the voltage range of 3.5V to 4.85V, the battery was charged to 4.85V at a constant current of 1C, then charged to a cut-off current of 0.05C at a constant voltage, and then discharged to 3.5V at a constant current of 1C for a cycle life test, with 300 cycles.

[0112] The performance test results are shown in Table 1.

[0113] Table 1: Comparison of material performance tests in Examples 1-7 and Comparative Examples 1-2

[0114]

[0115] From Table 1, we can see the effect of Si3N4-OPSZ coating on battery capacity and cycle performance:

[0116] First, compared with Comparative Example 1, the discharge specific capacity of the battery assembled with Si3N4-OPSZ coated PE diaphragm is slightly lower, indicating that the diaphragm has a certain negative impact on the battery capacity, but it is not obvious; secondly, after 300 cycles, it was found that the capacity retention rate of the battery assembled with Si3N4-OPSZ coated PE diaphragm is higher, indicating that the Si3N4-OPSZ coated PE diaphragm is helpful for the battery cyclability, and the Si3N4 in the diaphragm is related to the HF reaction, which alleviates the impact of HF on battery performance.

[0117] In addition, according to the DCR results, the presence of the Si3N4-OPSZ coating will lead to an increase in the internal resistance of the battery, which also explains why the discharge specific capacity of the Si3N4-OPSZ-coated PE diaphragm assembled battery is slightly lower. However, after 300 cycles, the discharge DCR of the Si3N4-OPSZ-coated PE diaphragm assembled battery is lower, indicating that the Si3N4-OPSZ coating is beneficial to improving the cycle performance of the battery.

[0118] Among them, the acidity of the electrolyte was tested before and after the cycle, and it was found that the electrolyte acidity of the battery assembled with the Si3N4-OPSZ coated diaphragm was lower after the cycle. The results showed that the Si3N4-OPSZ coating layer can indeed consume HF in the electrolyte and reduce the impact of HF on battery performance. Through DSC characterization, it was found that the melting transition temperature of ordinary PE diaphragm is 135℃, while the melting transition temperature of Si3N4-OPSZ coated diaphragm is 380℃, which is significantly higher than PE diaphragm, indicating that the Si3N4-OPSZ coated diaphragm has excellent thermal stability; finally, through the hot box test, it was found that the soft pack battery assembled with Si3N4-OPSZ coated diaphragm can pass the 140℃ hot box test, indicating that the use of Si3N4-OPSZ coated diaphragm can improve the safety of the battery.

[0119] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium-ion battery separator, comprising a base film and a coating; the base film comprises a first surface and a second surface facing opposite to the first surface, characterized in that: The coating is coated on the first surface and the second surface, and the coating includes polysilazane and Si3N4.

2. The lithium ion battery separator according to claim 1, characterized in that The mass proportion of Si3N4 in the coating is 8% to 12%.

3. The lithium ion battery separator according to claim 1, characterized in that: The Si3N4 in the coating is prepared by partial cleavage of the polysilazane.

4. The lithium ion battery separator according to claim 1, characterized in that The coating has a thickness of 1.5 to 3.0 μm.

5. The lithium ion battery separator according to claim 1, characterized in that The base film has a thickness of 7 to 12 μm.

6. The lithium ion battery separator according to claim 1, characterized in that The base film is PP or PE.

7. A method for manufacturing a lithium ion battery separator, characterized in that: The steps include: S1 takes a certain amount of polysilazane, partially cracks it under a nitrogen atmosphere, and then crushes and grinds it to obtain a composition of polysilazane containing Si3N4; S2: dispersing the composition in an aqueous solvent containing a dispersant, and then adding a thickener, a binder and a wetting agent to the water respectively, and stirring to obtain a stable diaphragm coating slurry; S3: coating the separator coating slurry on both sides of the base film and drying the moisture to obtain the lithium ion battery separator.

8. The manufacturing method according to claim 7, characterized in that: In the step S1, the mass proportion of Si3N4 in the composition is 8% to 12%, and / or, after grinding, the particle size of the composition is 20 to 80 nm.

9. The manufacturing method according to claim 7, characterized in that: The mass ratio of the composition: dispersant: thickener: binder: wetting agent is 80-120:1:10:10:1; and / or the solid content of the diaphragm coating slurry is 40%-60%.

10. A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, and a lithium ion battery separator as claimed in any one of claims 1 to 6 spaced between the positive and negative electrode sheets, characterized in that: The lithium-ion battery separator is prepared by the method according to any one of claims 7 to 9.